One judge to rule them all: single-member courts as an answer to delays in criminal trials - Kalliris, Konstantinos; Alysandratos, Theodore (Journal of empirical legal studies, 2023)
This paper is a discussion of whether single-member judicial panels are an effective way of accelerating the delivery of criminal justice. We use a reform which introduced single-member courts in Greece, where delays in court proceedings are common according to the European Justice Scoreboard and the European Court of Human Rights. We use a novel dataset of 1463 drug trafficking cases tried between June 2012 and January 2014. As our measure of efficiency we use the time to issue a decision, and we find that single-member panels are as efficient as three-member ones. We take advantage of a feature of the reform to control for several confounding factors and support a causal interpretation of our findings. We complement our analysis with a survey of 142 judges to guide our interpretation of the results.